Paleo- and rock magentic data of core PS97/085-3 - Jiabo Liu (PANGAEA, 2025)
During Expedition PS97 of the Research Vessel POLARSTERN to the Drake Passage in 2016, three sediment cores, PS97/085-3, PS97/084-1, and PS97/079-2 were collected along the Shackleton Fracture Zone. The age model of core PS97/085-3 was constructed using a combination of radiocarbon dating and tie points from paleomagnetic and environmental tuning (refer to https://doi.org/10.1594/PANGAEA.923843). The age models of cores PS97/084-1and PS97/079-2 were determined by tuning their rock magnetic parameters to those of core PS97/085-3. Rock magnetic results indicate that the magnetic minerals in the three sediments cores are dominated by (titano-)magnetite and have well-preserved geomagnetic signals. This dataset includes rock magnetic results of bulk magnetic susceptibility, anhysteretic remanent magnetization (ARM), and saturated Isothermal remanent magnetization (SIRM), and paleomagnetic results of characteristic inclination and declination, natural remanent magnetization (NRM) after alternating field (AF) field of 30 mT (NRM30mT), and relative paleointensity (RPI). RPIs are determined by NRM30mT/SIRM for cores PS97/084-1, and PS97/079-2, and by ln(NRM30mT)/ARM for core PS97/085-3.